Class as a semiotic resource in consumer advertising: Markedness, heteroglossia, and commodity temporalities. (September 2014) - Callier, Patrick
This article critically examines the mass-mediated portrayal of social class and commodity formulation in a corpus of US television advertisements for the Ford F-150 pickup truck, aired in 2007. The use of stereotypical diacritics of white-collar and blue-collar social identities in the ads circulates a representation of class identities as consumer categories, even as the ads' portrayals of class difference reproduce hegemonic relationships of markedness between 'middle-class' consumers and other social categories. Examining representations of different phases of commodity formulation and social voices loosely associated with these phases, I show how various social identities are subjugated to the commercial ends of the advertising encounter, and how the advertisements both induce consumer behavior as well as reshape hegemonic understandings of social difference and inequality.